MEMBANGUN TEORI MANAJEMEN PENDIDIKAN ISLAM MELALUI KAJIAN FILSAFAT ILMU - Satria Utama, Fajar; Ananda Putri, Rizky; Falah, Fakhriy; Hidayat, Wahyu (Jurnal Manajemen Pendidikan, 2023)
The focus of this research is the philosophy of science, epistemology, methodology, logic, ethics, and aesthetics related to the management of Islamic education.This research is expected to contribute to the formation of a solid theoretical foundation for the management of adaptive Islamic education in line with the principles of Islamic science through the integration of the concepts of philosophy of science. This research is expected to contribute to the formation of a solid theoretical foundation for managing Islamic education that is adaptive and consistent with the principles of Islamic science through the integration of concepts of philosophy of science. This research shows that the philosophy of science provides a deeper understanding of the characteristics of science, which allows the formation of theories based on empirical experience and systematic research. Keywords: philosophy of science, theory of management of Islamic education.